Burden of Eating Disorders in China, 1990-2019: An Updated Systematic Analysis of the Global Burden of Disease Study 2019 - Li, Zhitao; Wang, Lili; Guan, Haixia; Han, Cheng; Cui, Peng; Liu, Aihua; Li, Yongze (Frontiers in Psychiatry, 2021)
Background: Eating disorders, including anorexia nervosa (AN) and bulimia nervosa (BN), are complex mental disorders. A better understanding of the burden of eating disorders is essential for improving their management. Information about the burden of eating disorders at the national level in China remains unclear. Methods: This is a systematic analysis of the Global Burden of Disease Study (GBD) 2019. The sex- and age-specific prevalence, incidence, and disability-adjusted life years (DALYs) of eating disorders in China were estimated by systematically reviewing all available epidemiological data and inputting these data into a Bayesian meta-regression tool (DisMod-MR 2.0). Trends in the age-standardized prevalence, incidence, and DALYs due to AN and BN were assessed from 1990 to 2019. Results: The age-standardized incidence rate (ASIR), prevalence rate (ASPR), and DALY rate per 100,000 population were estimated to be 13.22 (95% UI, 9.35–18.23), 38.08 (95% UI: 26.37–55.73), and 8.38 (95% UI, 4.87–13.35) for AN and 130.05 (95% UI, 84.02–187.13), 75.21 (95% UI, 48.52–105.97), and 16.16 (95% UI, 9.23–25.40) for BN, respectively, in 2019. The prevalence, incidence, and DALY rate of AN peaked at 15–19 years old. The prevalence and DALY rate of BN peaked at 30–34 years old. Females had a higher burden of AN and a lower burden of BN than males. The ASIR, ASPR, and DALY significantly increased by 1.3% (95% CI: 1.3–1.4%), 1.6% (95% CI, 1.5–1.6%), and 1.6% (95% CI, 1.5–1.7%) for AN and 1.4% (95% CI: 1.4–1.4%), 2.0% (95% CI, 2.0–2.1%), and 2.0% (95% CI, 2.0–2.1%) for BN, respectively, from 1990 to 2019 in China. In addition, the increments in all the age-standardized measures of BN were higher in males than in females. Conclusions: The burden of eating disorders in China showed unexpected patterns that varied by sex and age, with increasing trends of AN and BN from 1990 to 2019. More attention should be given to improving the burden of BN in males in China.